Viscoelastic characterization of an EPDM rubber and finite element simulation of its dry rolling friction (eXPRESS Polymer Letters)
The viscoelastic properties of an ethylene/propylene/diene rubber (EPDM) containing 30 parts per hundred parts rubber [phr] carbon black (CB) were determined by dynamic mechanical thermal analysis (DMTA) measurements. A 15-term Maxwell-model was created to describe the time-dependent material behavior of this rubber. The frictional behavior under dry rolling conditions was studied on a home-built rolling ball (steel)-on-plate (rubber) (RBOP) test rig. Both normal and tangential forces were detected during the measurements. The rolling test was simulated with the MSC.Marc finite element (FE) software using the evaluated viscoelastic material properties. Results of the experimental tests and of the simulation were compared and a good agreement was found between them.